Influence of Regulated Deficit Irrigation on Arbequina’s Crop Yield and EVOOs Quality and Sensory Profile - Sastre, Blanca; Arbonés, Amadeu; Pérez-Jiménez, María Á.; Pascual, Miquel; Benito, Alejandro; Lorenzo, Cristina; Villar Mir, Josep M.; Bonet, Luis; Paz, Sergio; Santos, Ángel; Hermoso, Juan Francisco; Romero, Agustí; et al. (MDPI, 2023)
Regulated deficit irrigation in super-high-density (SHD) olive orchards is a well-known strategy to save water and control plant vigor, without decreasing fruit or oil yield. As there is controversial information about its influence on virgin olive oil quality, a trial was conducted in five SHD olive orchards of Arbequina cultivar in different locations of central, east, north and northeast Spain under full irrigation (FI) and regulated deficit irrigation (RDI) treatments. RDI applied during phase II of fruit growing (40% of total needs) saves more than 20% of water on average, without reductions in olive fruit or extra virgin olive oil (EVOO) yield. No threshold of 3.5 MPa of stem water potential was crossed in any case. RDI modified sterols and the fatty acid profile of EVOOs but not phenols, quality parameters, or the sensory profile. Latitude, altitude, and yearly rainfall have a big impact on some compounds such as campesterol, oleuropein, or margaroleic or linolenic acids.